AIRLINES: WHAT EXPLAINS THE CHOICE OF BRAZILIAN TOURISTS? - Gervasoni, Viviane Chunques; Rossi, George Bedinelli (Seven Editora, 2026)
According to the Logistics Bulletin released by the National Civil Aviation Agency (ANAC), air transport accounted for almost 70% of interstate travel on regular routes in 2019. In the Planned Behavior Theory (PBT) model, behavioral intention is directly influenced by three components: attitudes, subjective norms, and perceived behavioral control (Ajzen, 1991). Although PBT has been used in many studies related to transportation (Hsiao; Yang, 2010; Jing et al., 2014), it has limited application in passenger research in the LCC (low-cost carrier) market. Therefore, this research aimed to expand the theory of planned behavior focusing on Brazilian low-cost airlines. The results showed that PBT, when applied to understanding Brazilian low-cost airlines, has the following explanatory variables: risk, quality, and frequency.